Changing employment dynamics within the creative city: Exploring the role of 'ordinary people' within the changing city landscape. (November 2020) - Baum, Tom
This article is about creative cities and their largely invisible and largely neglected workforce, the 'ordinary people' who provide the work- and life-place services upon which creative workers depend. The article considers the nature of creative cities, their labour markets and the precarious nature of much employment within them. The ambiguous relationship between different employment groups within the creative city is illustrated. The analysis forms the basis for reaching conclusions and helping to formulate advice for policy makers in developing approaches that are inclusive and accessible. The article is set against and acknowledges the importance of the rising tide of populism as a real challenge to an elitist mainstream creative city discourse.